Re-examining the reliability and validity of 30-15IFT for VO2max prediction in male collegiate soccer players: a pilot study - Cheng, R.; Lin, W.; Song, L.; Pan, J.; Wang, N.; Li, X. (Frontiers in Physiology, 2025)
Purpose: This pilot study aimed to determine the reliability and validity of the 30-15 Intermittent Fitness Test (30-15IFT) in male collegiate soccer players. A secondary aim was to develop a new, population-specific equation for predicting maximal oxygen uptake (VO2max) and to compare its predictive validity against a widely used general equation.